THE EFFECT OF CLASSROOM MANAGEMENT ON STUDENTS’ LEARNING ACTIVENESS AT SD NEGERI LAMPEUNEURUT ACEH BESAR - Rahima Ahsana; Lailatussaadah Lailatussaadah; Nurmayuli Nurmayuli; Sri Mutia (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to examine the effect of classroom management on students’ learning activeness at SD Negeri Lampeuneurut, Aceh Besar. The study employed a quantitative approach using a simple linear regression design. The population consisted of all fifth-grade students totaling 98 students, with a sample of 80 students selected using the Krejcie and Morgan table. Data were collected through a questionnaire measured using a Likert scale and analyzed using regression analysis with SPSS 25. The results showed that classroom management was in the high category with a mean score of 3.85, and students’ learning activeness was also in the high category with a mean score of 3.80. Regression analysis indicated a significant effect of classroom management on students’ learning activeness, as evidenced by a significance value of 0.001 < 0.05, a correlation coefficient of 0.478, and a coefficient of determination of 22.8%. The regression equation Y = 21.963 + 0.690X indicates that every one-unit increase in classroom management increases students’ learning activeness by 0.690 units. Thus, it can be concluded that effective classroom management has a significant positive effect on improving students’ learning activeness at SD Negeri Lampeuneurut, Aceh Besar